2012
DOI: 10.1186/1479-5876-10-169
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive cell therapy with autologous tumor infiltrating lymphocytes and low-dose Interleukin-2 in metastatic melanoma patients

Abstract: BackgroundAdoptive cell therapy may be based on isolation of tumor-specific T cells, e.g. autologous tumor infiltrating lymphocytes (TIL), in vitro activation and expansion and the reinfusion of these cells into patients upon chemotherapy induced lymphodepletion. Together with high-dose interleukin (IL)-2 this treatment has been given to patients with advanced malignant melanoma and impressive response rates but also significant IL-2 associated toxicity have been observed. Here we present data from a feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 35 publications
2
116
1
Order By: Relevance
“…Moreover, cell suspensions obtained from fresh tumors in these prior studies were often processed with layered Ficoll gradients to enrich in lymphoid cells prior to culture initiation, and it had not been demonstrated that TILs could be expanded from tumor fragments as we have now described. Additionally, these prior studies did not test whether GI TILs could be expanded to numbers and with methods currently used in ACT protocols in melanoma patients (5)(6)(7)(8). Interestingly however, the higher fractions of CD8 + TILs in prior studies compared with our study suggests that preferential expansion of T cell subsets may be achieved by changing culture techniques and mitogenic stimuli.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Moreover, cell suspensions obtained from fresh tumors in these prior studies were often processed with layered Ficoll gradients to enrich in lymphoid cells prior to culture initiation, and it had not been demonstrated that TILs could be expanded from tumor fragments as we have now described. Additionally, these prior studies did not test whether GI TILs could be expanded to numbers and with methods currently used in ACT protocols in melanoma patients (5)(6)(7)(8). Interestingly however, the higher fractions of CD8 + TILs in prior studies compared with our study suggests that preferential expansion of T cell subsets may be achieved by changing culture techniques and mitogenic stimuli.…”
Section: Discussioncontrasting
confidence: 44%
“…Treatment goals for patients with metastatic melanoma are changing, given that the adoptive cell transfer (ACT) of autologous tumor-infiltrating lymphocytes (TILs) can mediate complete and durable cancer regression in patients with heavy disease burden, refractory to all other treatments (5). Cancer centers in and outside the United States have begun to offer this form of immunotherapy and report similar response rates, and multicenter trials are expected (6)(7)(8)(9). Although the efficacy of TIL-based ACT may be linked to the more immunogenic nature of melanoma compared with other solid cancers, it remains to be determined whether this approach can be adapted for the treatment of common epithelial tumors, such as metastatic GI adenocarcinomas.…”
mentioning
confidence: 99%
“…We recently published the results from a small pilot study in which 6 patients received classical lymphodepleting chemotherapy and TIL transfer followed by a low-dose subcutaneous (s.c.) IL2 regimen consisting of 2 MIU/day for 14 days (21). Two of these patients achieved complete, long-lasting responses suggesting that high-dose IL2 may not be required for obtaining durable clinical responses (21).…”
Section: Introductionmentioning
confidence: 95%
“…Two of these patients achieved complete, long-lasting responses suggesting that high-dose IL2 may not be required for obtaining durable clinical responses (21). Here we report the results from a clinical trial where 25 patients with metastatic melanoma were sequentially treated with TIL-ACT preceded by lymphodepleting chemotherapy and followed by an attenuated dose of IL2 administered in a continuous decrescendo regimen.…”
Section: Introductionmentioning
confidence: 96%
“…61 The readministration of TILs necessitates lymphodepletion through chemotherapy or wholebody radiation therapy. 23,61,71 Administration of TILs in combination with IL-2 resulted in an overall response rate of 34%-40% and increased progression-free survival in patients with metastatic melanoma. 36,71,90 These rates were similar in patients who were IL-2 naïve and in patients who had not responded to isolated IL-2 administration during previous therapy.…”
Section: Adoptive Cell Transfermentioning
confidence: 99%